For Palestine Essays from the Tom Hurndall Memorial Lecture Group - Parker, Ian (Open Book Publishers, 2023)
"I am not afraid to look." - Tom Hurndall, 2003. On the eve of the invasion of Iraq in February 2003, Tom Hurndall, a photography student at Manchester Metropolitan University, travelled from Manchester to the Middle East to witness the horrors in Iraq and then later in Palestine. Tom was shot in the head by an Israeli soldier on 11 April 2003 whilst attempting to rescue two children trapped by Israeli sniper fire. He later died in hospital on 13 January 2004 without gaining consciousness. He is remembered for his determination to bear witness to the conflict in Palestine and his bravery to capture the atrocities directed towards the suppression of the Palestine people. This book is a collection of lectures written by reputable scholars who offer diverse perspectives on the historical, political and cultural struggles in Palestine. Encompassed in the pages are sixteen chapters produced for the Tom Hurndall Memorial Lecture Group. Unlike predecessors of this topic, this book offers a thought-provoking and comprehensive analysis of Palestine, including architectural, cultural, legal, sociological, and psychological questions, providing a larger scope of study that has not yet been done before. Ultimately, this book explores oppression in Palestine and beyond in the Middle East. The vast study and in-depth exploration makes this an ideal book for those who are interested in the Palestine conflict, Zionism, Israel and further conflict in the Middle East, as well as a necessity for those who are studying the topic in education settings.